Review on Health Benefits of Peanut (International Journal of Innovative Research in Engineering & Management, 2023)
Peanuts are popular crop produced all  over globe. Apart from oil, peanut by-products include  numerous additional useful components such as proteins,  polyphenols, fibers, vitamins, antioxidants, & mineral that  might added as function ingredients to many processed  meals. Peanuts are abundant in compounds like resveratrol,  acid, quercetin, & phytosterols, which aid to limit  cholesterol absorption from diet, according to new research. It's also rich in Co-enzyme Q10&includes all 20 amino  acids, with arginine being most abundant. These bioactive  chemicals have been shown to have disease-fighting effects & are believed to help people live longer. Content of these  beneficial chemicals has increased as result of processing  techniques such as roasting & boiling. Purpose of this  article is to provide review of peanut bioactive  components.
Keywords: Crop; Functional Ingredients; Health Benefits; Peanut; Seeds